Policing normalcy: sexual violence against women offenders with disability. Issue 3 (4th May 2017) - Steele, Linda
Abstract: This article explores police responses to sexual violence reported by women offenders designated as having cognitive and psychosocial disabilities. The article does so by reference to the critical disability studies analytical approach to disability as socially constructed 'abnormality'. This article utilizes this approach in analysing the recorded police contacts of one woman offender designated as disabled, 'Jane'. Jane has had multiple contacts with police over a period of 15 years as a victim of sexual violence, alleged offender and 'mentally ill' person. The article finds that through multiple contacts with police as victim, alleged offender and 'mentally ill' person, the police events records build a narrative of Jane as an 'abnormal' body who is reduced to a drain on police and public health resources, a dishonest and nuisance offender and an attention seeker. The article argues that it is the interlocking discourses of gender, disability and criminality that produce Jane as unworthy of victim status and, perversely, in need of punishment by the criminal justice system for her public displays of trauma, mental distress and requests for police assistance. Ultimately, the article concludes that we need to give greater attention to the relationship between disability and affect, and to the broader cultural, institutional, legal and economic discourses that shape individuals' affective responses, in understanding police responses to violence against women offenders designated as disabled and in contesting these women's status as 'ungrievable' victims of violence.